Persepsi Followers dalam Media Sosial Tiktok Terhadap Akun @Mas Dolan Sebagai Media Referensi Wisata (Studi Kualitatif pada followers di wilayah karanganyar) - Yuliana Safitri, Ernawati; Hindra Hastuti, Nurnawati; Sihabuddin, Sihabuddin (Solidaritas, 2024)
Abstract The use of TikTok as a tourist reference media has become an effective role compared to old media so that it raises various perceptions for users who access. The tiktok mas dolan account is an account that can present content for tourist destinations that are hidden gems. So that from the many references available, it often causes perceptions among followers about the use of social media which is not only an entertainment medium. This study aims to analyze how followers perceive the Mas Dolan account on social media TikTok as a tourist reference medium. Using the theory of perception proposed by Bernard Berelson which is divided into 3, namely sensation, attention and interpretation. The research method used is qualitative to observe the phenomenon being studied using interviews, observations and documentation. The result of this study is that informants feel positive about the existence of a mas dolan account with a visual appearance in its content by adding a narrative that is quite interesting so that it can provide detailed information, add insight into tourist attractions that are rarely known, and can open relationships between their followers. Keywords: perception, followers, tiktok social media